Analysis of vehicle parking potential in Sumbawa regency - Suprianto, Suprianto; Pamungkas, Binar Dwiyanto (Jurnal Ekonomi, 2024)
This research aims to determine the potential for parking revenue based on the number of vehicles, rates, working days and parking revenue collection costs in Sumbawa Regency. The type of research used is descriptive, the research sample is parking points based on the level of visitor crowds, shopping centers, visitor intensity, location of the research object, and the proximity of one object to another. The locations for this research are 13 locations or parking points in Sumbawa Regency. The analytical tool used in this research is Quantitative Analysis where the potential for parking levies or taxes is calculated according to the potential revenue of each point. The research results show that the gross potential (gross) parking revenue for 13 parking locations in Sumbawa Regency amounts to an average of IDR 542,436 per day per location. So in one year (363 days) for these 13 parking locations the potential for receiving parking fees is Rp. 2,559,756,729,-. The largest potential parking levy comes from the Seketeng Market parking levy, which is an average of IDR 1,613,143 per day. And Jl. Kartini amounting to Rp. 1,492,000.-, The net potential (net) of parking revenues for 13 parking locations in Sumbawa Regency amounts to an average of IDR 273,607,- per day per location. So in one year (363 days) for these 13 parking locations the potential for receiving parking fees is Rp. 1,291,149,514,-. The largest potential parking levy comes from the Seketeng Market parking levy, which is an average of IDR 806,571 per day. and Jl. Kartini amounting to Rp. 746,000,-.